2022
DOI: 10.1016/j.anndiagpath.2021.151881
|View full text |Cite
|
Sign up to set email alerts
|

The histologic and molecular correlates of liver disease in fatal COVID-19 including with alcohol use disorder

Abstract: Hepatic disease is common in severe COVID-19. This study compared the histologic/molecular findings in the liver in fatal COVID-19 ( n = 9) and age-matched normal controls (n = 9); three of the fatal COVID-19 livers had pre-existing alcohol use disorder (AUD). Controls showed a high resident population of sinusoidal macrophages that had variable ACE2 expression. Histologic findings in the cases included periportal/lobular inflammation. SARS-CoV2 RNA and nucleocapsid protein were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Although it is logical to assume there is more than one molecular mechanism, it was initially hypothesized that systemic spread of SARS-CoV2 infection from the lung and nasopharynx to the brain was the primary mechanism. However, many studies have documented that SARS-CoV2 RNA is rarely found in the bloodstream even in fatal COVID-19 and, importantly, the viral RNA is not detected in the brain in such cases [7] , [8] , [9] , [10] . As examples, qRT-PCR assays failed to detect SARS-CoV2 RNA in the CSF of COVID-19 patients with neurological complications [51] , and a larger study also indicated that viral RNA was not present in the brain in fatal COVID-19 cases, despite the widespread microvascular damage [52] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is logical to assume there is more than one molecular mechanism, it was initially hypothesized that systemic spread of SARS-CoV2 infection from the lung and nasopharynx to the brain was the primary mechanism. However, many studies have documented that SARS-CoV2 RNA is rarely found in the bloodstream even in fatal COVID-19 and, importantly, the viral RNA is not detected in the brain in such cases [7] , [8] , [9] , [10] . As examples, qRT-PCR assays failed to detect SARS-CoV2 RNA in the CSF of COVID-19 patients with neurological complications [51] , and a larger study also indicated that viral RNA was not present in the brain in fatal COVID-19 cases, despite the widespread microvascular damage [52] .…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the latter protein, a key player in the blood brain barrier, has been proposed as a biomarker of Alzheimer's disease per se even in the absence of COVID-19 [42] . BCL6, BACH1, SHIP1, and BCL10 were chosen for study as each are targets of miR-155 , which we have shown is increased in the cells after the endocytosis of SARS-CoV2 spike protein [9] . Further, though miR-155 is not dysregulated in Alzheimer's disease, there was a relative decrease in BCL6 and BCL10 in the Alzheimer's disease brains versus controls [57] although the decrease was more pronounced in the COVID-19 brain tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although comparisons of liver histology after COVID-19 infection between NAFLD versus controls have not been performed, a recent study reported histologic differences in fatal COVID-19 between patients with versus without alcohol use disorder (AUD). Specifically, people with AUD demonstrated not only 10-fold increased expression of ACE2 + cells, but also greater number of cells positive for viral spike protein compared to people without AUD [42]. Injection of the S1 subunit of spike protein in mice induced hepatic lobular inflammation [42].…”
Section: Direct Effectsmentioning
confidence: 99%
“…Specifically, people with AUD demonstrated not only 10-fold increased expression of ACE2 + cells, but also greater number of cells positive for viral spike protein compared to people without AUD [42]. Injection of the S1 subunit of spike protein in mice induced hepatic lobular inflammation [42]. The discrepancies between studies may partially be explained by differences in the duration of infection, in patient characteristics, as well as in the post-mortem processing of the autopsy samples.…”
Section: Direct Effectsmentioning
confidence: 99%